THE DEVELOPMENT OF SPIRNT LEARNING MODEL BASED GAME IN ELEMENTARY SCHOOL - Andriyan, Novan (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to produce an effective, valid, and practical learning model. This research method is Research and Development (R & D). The data were collected by questionnaires from teacher evaluation and questionnaires by students. The results of the experiments for the validity of the small group test were obtained on average percentage (84%), whereas in the large group trial showed the prevalence rate obtained by the average percentage (78%), the product had good category validity. To see the practicality of the results of the students' questionnaires after conducting the trials, small group trials got an average percentage of 78.8% and large group trials were 81% and thus the practicality level was good. To see the effectiveness of the product from the aspect of motivation, the results of small group trials show the relationship of motivation aspect is 70.8% and large group trials are 71.2% of the cognitive, affective, and psychomotor aspects. From these results, the tested product tried to show the effectiveness of the good category. Thus the development of sprint learning model based game in elementary school has been effective so that it can apply it in the learning of physical education.